2022
DOI: 10.3390/pathogens11020149
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Melioidosis and Its Association with Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Melioidosis is an under-recognized fatal disease in humans, caused by the Gram-negative bacterium Burkholderia pseudomallei. Globally, more than 35,000 human melioidosis cases have been reported since 1911. Soil acts as the natural reservoir of B. pseudomallei. Humans may become infected by this pathogen through direct contact with contaminated soil and/or water. Melioidosis commonly occurs in patients with diabetes mellitus, who increase the occurrence of melioidosis in a population. We carried out a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 107 publications
0
19
0
1
Order By: Relevance
“… Burkholderia pseudomallei is a pathogenic saprophyte that causes melioidosis ( 1 ). The disease is endemic in Malaysia, with various clinical presentations ( 2 , 3 ), and its management includes 6 months of antibiotic regimen administration ( 4 ). Clinical specimens were collected from patients suspected of bacteremia in accordance with ethical approvals (International Islamic University Malaysia [IIUM] Research Ethics Committee [IREC] and National Medical Research Register [NMRR] via IREC 2021-193, NMRR-17-3238-39448, and NMRR-21-360-58751).…”
Section: Announcementmentioning
confidence: 99%
“… Burkholderia pseudomallei is a pathogenic saprophyte that causes melioidosis ( 1 ). The disease is endemic in Malaysia, with various clinical presentations ( 2 , 3 ), and its management includes 6 months of antibiotic regimen administration ( 4 ). Clinical specimens were collected from patients suspected of bacteremia in accordance with ethical approvals (International Islamic University Malaysia [IIUM] Research Ethics Committee [IREC] and National Medical Research Register [NMRR] via IREC 2021-193, NMRR-17-3238-39448, and NMRR-21-360-58751).…”
Section: Announcementmentioning
confidence: 99%
“…Patients with diabetes are three times more likely to develop melioidosis than patients without diabetes, which is related to the fact that hyperglycaemia can damage neutrophils and lymphocytes and destroy phagocytes and immune function. As persistent hyperglycaemia further worsens the condition of melioidosis, the aggravation of melioidosis also leads to poor blood sugar control, forming a vicious cycle [ 17 , 18 ]. Most of the cases in our study also occurred in coastal areas and during the rainy season in summer and fall, which is consistent with the case reports in Hainan, China [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by a recent study in Perak, Malaysia, which found that 71.1% of patients have diabetes mellitus [ 67 ]. Patients with diabetes mellitus were three times more likely to be infected by melioidosis than non-diabetic patients [ 68 ]. Interestingly, diabetes mellitus with soil and water exposure results in higher OR values compared with single variables, which highlights those individuals exposed to more risk factors are highly vulnerable to B. pseudomallei infection.…”
Section: Discussionmentioning
confidence: 99%